Evaluation of four clinical decision rules in children with minor head trauma: NEXUS II, PECARN, CHALICE, and CATCH - Majid Zamani; Farhad Heydari; Farzin Feyzollahi; Mehrdad Esmaillian; Amir Bahador Boroumand (Archives of Trauma Research)
Background: Clinical decision rules could potentially help emergency department (ED) trauma triage, allowing clinicians to prioritize treatment for the most severely injured patients.Objectives: This study evaluated and compared the diagnostic accuracy of the National Emergency X-radiography Utilization Study II (NEXUS II), the Pediatric Emergency Care Applied Research Network (PECARN), the Canadian Assessment of Tomography for Childhood Head Injury (CATCH), and the Children’s Head Injury Algorithm for the Prediction of Important Clinical Events (CHALICE) in identifying intracranial injury (ICI) in children with minor head trauma.Methods: This prospective, cross-sectional, descriptive-comparative study was conducted on children with mild head trauma who presented to the ED. Inclusion criteria were age under 16 years, Glasgow Coma Scale (GCS) score of ≥14, and the requirement of a head Computed Tomography (CT) scan as a part of their examination. The primary outcome was the presence of pathological findings on the CT scan. The predictive value of the four rules was evaluated using the receiver operating characteristic (ROC) analysis.Results: Among the 340 children studied, 25 (7.4%) had an intracranial injury, and six patients (1.8%) required neurosurgical intervention. The mean age was 7.96 ± 4.11 years (60.9% boys). The sensitivities for predicting a positive head CT were 96.0% (95%CI 79.6– 99.9) for the NEXUS II and PECARN rules, and 92.0% (95%CI 73.9–99.0) for the CATCH and CHALICE rules. Additionally, the negative predictive values (NPV) for these rules were 99.5% (95%CI 96.4–99.9) for the NEXUS II, 99.4% (95%CI 96.2–99.9) for the PECARN, and 98.8% (95%CI 95.8–99.7) for the CATCH and 98.8% (95%CI 95.7–99.7) for the CHALICE. Notably, one of the 25 patients who had pathologic findings on CT met none of the diagnostic criteria of all the rules and did not require neurosurgical intervention.Conclusion: All four clinical decision rules demonstrated strong accuracy in identifying pediatric patients with abnormal CT findings, showing excellent sensitivities and NPVs, which supports their suitability for evaluating mild head trauma in the ED.